2017
DOI: 10.1111/jvim.14808
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐Free DNA and DNase Activity in Dogs with Immune‐Mediated Hemolytic Anemia

Abstract: Background: Immune-mediated hemolytic anemia (IMHA) in dogs has a high risk of thrombosis and is associated with marked neutrophilia and necrosis. Cell death and release of neutrophil extracellular traps contribute to increased serum concentrations of cell-free DNA, and in human autoimmune disease reduced DNase activity further increases cell-free DNA. Free DNA in blood has prothrombotic properties and could contribute to hypercoagulability in IMHA.Hypothesis: Cell-free DNA is elevated and DNase activity reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 63 publications
0
27
0
Order By: Relevance
“…cfDNA is an attractive biomarker in human medicine and particularly in oncology. Thus, it has also been evaluated in different canine diseases 16,17,19,20,[50][51][52][53] . As in human, cfDNA concentration in dogs is correlated with the severity of the disease and prognosis 16,17,20,53 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…cfDNA is an attractive biomarker in human medicine and particularly in oncology. Thus, it has also been evaluated in different canine diseases 16,17,19,20,[50][51][52][53] . As in human, cfDNA concentration in dogs is correlated with the severity of the disease and prognosis 16,17,20,53 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has also been evaluated in different canine diseases 16,17,19,20,[50][51][52][53] . As in human, cfDNA concentration in dogs is correlated with the severity of the disease and prognosis 16,17,20,53 . Consistently with previous studies, we found that dogs with multicentric lymphoma had significantly higher concentration of total cfDNA than healthy dogs, dogs with non-cancerous diseases and dogs with other cancers 20,51 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant increase in the blood concentration of cfDNA was found in diseased dogs, as compared to healthy dogs, and a positive association between cfDNA concentration and disease severity and survival was observed . Both dogs with sepsis and those with moderate‐to‐severe trauma had significantly increased cfDNA concentrations compared to healthy dogs, and cfDNA concentration was associated with death in dogs with immune‐mediated hemolytic anemia …”
mentioning
confidence: 94%
“…21 22 and cfDNA concentration was associated with death in dogs with immune-mediated hemolytic anemia. 23 A short half-life and a good correlation with disease severity would render cfDNA a useful tool to quantify the extent of tissue injury. Based on current knowledge, we hypothesized that, in dogs, cfDNA would have a short biological half-life and its concentration would be able to stratify mild, moderate, and severe tissue injury.…”
mentioning
confidence: 99%